2022
DOI: 10.3390/membranes12040371
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Microplastics in Waste Sludge of Wastewater Treatment Plants: Comparison between Membrane Bioreactor (MBR) and Conventional Activated Sludge (CAS) Technologies

Abstract: In this study, the presence of microplastics in the sludge of three wastewater treatment plants (WWTPs) was examined. The investigated WWTPs operated based on a conventional activated sludge (CAS) process, with (W1) or without (W2) primary clarification, and a membrane bioreactor process (MBR) (W3). The microplastics (MPs) concentration in the samples of W3 was approximately 81.1 ± 4.2 × 103 particles/kg dry sludge, whereas MPs concentrations in W1 and W2 were 46.0 ± 14.8 × 103 particles/kg dry sludge and 36.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The highest MPs removal efficiency (99.9%) was reported for membrane bioreactor (MBR) processes [36,37]. A recent Italian study [38] analyzing three WWTPs demonstrated that MBR technology allows to greatly improve (up to 76%, compared to active sludge with or without primary settling) the concentration of MPs in the sludge. Considering the consequent phases of state-of-the-art WWT, mostly based on active sludge processes, it was reported [19,31] that 35-59% of MPs are removed through preliminary treatments, 50-98% via primary settling, up to 20% through secondary settling, and that about 2% residual MPs can be detected in the effluent.…”
Section: Introductionmentioning
confidence: 99%
“…The highest MPs removal efficiency (99.9%) was reported for membrane bioreactor (MBR) processes [36,37]. A recent Italian study [38] analyzing three WWTPs demonstrated that MBR technology allows to greatly improve (up to 76%, compared to active sludge with or without primary settling) the concentration of MPs in the sludge. Considering the consequent phases of state-of-the-art WWT, mostly based on active sludge processes, it was reported [19,31] that 35-59% of MPs are removed through preliminary treatments, 50-98% via primary settling, up to 20% through secondary settling, and that about 2% residual MPs can be detected in the effluent.…”
Section: Introductionmentioning
confidence: 99%
“…MPs originate from various sources, including the breakdown of more extensive plastic materials and intentional discharge into the environment. Studies have shown varying concentrations, colors, and shapes of MPs in sludge [16][17][18][19]. Most MPs discovered in wastewater consist of fibers, pieces, and granules, indicating their varied sources.…”
Section: Mps In Wastewater Sludge: Sources Pathways and Characteristicsmentioning
confidence: 99%
“…Currently, conventional wastewater treatment procedures are used, while modifications to adapt for MP removal are continuously being explored and implemented. In general, removal of MPs in WWTPs is carried out in primary, secondary, and tertiary treatments, using one or a combination of the following procedures: skimming and sedimentation [68], dissolved air flotation filtration [69], sand filtration [70], biofiltration [71], membrane filtration [72,73], coagulation [74], ozonation [75], adsorption [76], magnetic extraction [77], membrane bioreactor (MBR) [78], conventional activated sludge [16], and degradation using microorganisms [79,80].…”
Section: Mps Removal Strategies In Wwtpsmentioning
confidence: 99%
“…This mismatch results in the underestimation of MPs in the sludge and effluent that are released into the environment. Therefore, sludge and effluent were identified as primary carriers of 'unaccounted' MPs in our ecosystems [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%